Early Minimally Invasive Removal of Intracerebral Hemorrhage (ENRICH): Study protocol for a multi-centered two-arm randomized adaptive trial - Ratcliff, Jonathan J.; Hall, Alex J.; Porto, Edoardo; Saville, Benjamin R.; Lewis, Roger J.; Allen, Jason W.; Frankel, Michael; Wright, David W.; Barrow, Daniel L.; Pradilla, Gustavo (Frontiers in Neurology, 2023)
Background Intracerebral hemorrhage (ICH) is a potentially devastating condition with elevated early mortality rates, poor functional outcomes, and high costs of care. Standard of care involves intensive supportive therapy to prevent secondary injury. To date, there is no randomized control study demonstrating benefit of early evacuation of supratentorial ICH. Methods The Early Minimally Invasive Removal of Intracerebral Hemorrhage (ENRICH) Trial was designed to evaluate the minimally invasive trans-sulcal parafascicular surgery (MIPS) approach, a technique for safe access to deep brain structures and ICH removal using the BrainPath® and Myriad® devices (NICO Corporation, Indianapolis, IN). ENRICH is a multi-centered, two-arm, randomized, adaptive comparative-effectiveness study, where patients are block randomized by ICH location and Glasgow Coma Score (GCS) to early ICH evacuation using MIPS plus standard guideline-based management vs. standard management alone to determine if MIPS results in improved outcomes defined by the utility-weighted modified Rankin score (UWmRS) at 180 days as the primary endpoint. Secondary endpoints include clinical and economic outcomes of MIPS using cost per quality-adjusted life years (QALYs). The inclusion and exclusion criteria aim to capture a broad group of patients with high risk of significant morbidity and mortality to determine optimal treatment strategy. Discussion ENRICH will result in improved understanding of the benefit of MIPS for both lobar and deep ICH affecting the basal ganglia. The ongoing study will lead to Level-I evidence to guide clinicians treatment options in the management of acute treatment of ICH. Trial registration This study is registered with clinicaltrials.gov (Identifier: NCT02880878).